Depression and Recovery of Daily Life Autonomy in Patients With Stroke Receiving Home Rehabilitative Treatment - Cataldo, Maria Concetta (Elmer Press, 2010)
BACKGROUND: The object of this study was to evaluate the prevalence of post stroke depression and its possible role as a predictive negative factor in patients receiving home rehabilitation treatment. METHODS: We analyzed 103 patients with stroke by correlating comorbidities, clinical and blood test parameters and characteristics of the lesion with depression class identified according to the Hamilton scale and the outcome of the rehabilitation program. RESULTS: A significant association between hypertension and post-stroke severe depression emerged in the female patients. CONCLUSIONS: Since the literature offers conflicting data, our results may contribute a stimulus for further studies. KEYWORDS: Home care; Rehabilitation; Stroke; Depression; Hypertension